Innovative use of a Montgomery cannula in the bronchoscopic management of tracheal stenosis and failed tracheostomy decannulation - Haidong Huang; Changming Chen; Harmeet Bedi; Chong Bai; Qiang Li; Wolfgang Hohenforst-Schmidt; Paul Zarogoulidis (Respiratory Medicine Case Reports, 2017)
Background: Endoprosthesis are being used in the everyday clinical practice either as a permanent solution or transient. They can be used in both benign and malignant situations. Case presentation: We report a case in which a temporary Montgomery cannula is used in conjunction with therapeutic bronchoscopy to manage a patient with failed tracheostomy decannulation secondary to a distal complex tracheal stenosis. Conclusions: This innovative use of the Montgomery cannula allowed for successful management of the patient's tracheal stenosis and subsequent tracheostomy tube decannulation.